Longitudinal assessment of dental erosion-abrasion by cross-polarization optical coherence tomography in vitro - Maria Jacinta Rosario Romero; Sávio José Cardoso Bezerra; Daniel Fried; Frank Lippert; George Joseph Eckert; Anderson Takeo Hara (Sociedade Brasileira de Pesquisa Odontológica, 2023)
Abstract: This study tested a novel in vitro dental erosion-abrasion model and the performance of cross-polarization optical coherence tomography (CP-OCT) in longitudinally monitoring the simulated lesions. Thirty human enamel specimens were prepared and randomized to receive three dental erosion-abrasion (EA) protocols: severe (s-EA, lemon juice/pH:2.5/4.25%w/v citric acid), moderate (m-EA, grapefruit juice/pH:3.5/1.03%w/v citric acid) and no-EA (water, control). EA challenge was performed by exposing the specimens to acidic solutions 4x/day and to brushing 2x/day with 1:3 fluoridated toothpaste slurry, for 14 days. Enamel thickness measurements were obtained using CP-OCT at baseline (D0), 7 (D7) and 14 days (D14) and micro-computed tomography (micro-CT) at D14. Enamel surface loss was measured with both CP-OCT and optical profilometry at D0, D7 and D14. Data was analyzed with repeated-measures ANOVA and Pearson's correlation (r) (α = 0.05). CP-OCT enamel thickness decreased over time in the s-EA group (D0 >D7 > D14, p < 0.001) and m-EA group (D0 > D14, p = 0.019) but did not change in the no-EA group (p = 0.30). Overall, CP-OCT and micro-CT results at D14 correlated moderately (r = 0.73). CP-OCT surface loss was highest for s-EA (p <0.001) but did not differ between moderate and no-EA (p = 0.25). Enamel surface loss with profilometry increased with severity (no-EA>m-EA>s-EA, p < 0.001). D14 surface loss was higher than D7 for both methods except for the no-EA group with profilometry. CP-OCT and profilometry had moderate overall correlation (r = 0.70). Our results revealed that the currently proposed in vitro dental erosion-abrasion model is valid and could simulate lesions of different severities over time. CP-OCT was a suitable method for monitoring the EA lesions.